Durable high early strength concrete via internal curing approach using saturated lightweight and recycled concrete aggregates - Qadri, Faisal A. F. (Kansas State University, 2020)
Environmental exposure is one of the primary causes of concrete pavement deterioration, specifically cyclic freezing and thawing, as is common in Kansas. Rehabilitation of deteriorated concrete pavement is a common pavement life-extension strategy, and a variety of rehabilitation techniques are often utilized depending on the level of pavement distress. Budgetary constraints, however, often dictate use of partial and full-depth patching methods to rehabilitate deteriorated concrete pavement rather than replace an entire road. For roadways with high traffic volume, patching is often done overnight within few hours. These repairs include removing the old concrete and preparing the location for new concrete, which must achieve at least 1,800 psi compressive strength 6 hours prior to opening to traffic to avoid compromising future durability. Current patches last less than 10 years despite a nominal 20-year service life. This study utilized an internal curing technique to produce durable high early strength concrete for patching. Because desorbing water throughout the concrete matrix improves the microstructure and reduces porosity, lightweight aggregates and crushed concrete aggregates were each used to desorb water and provide internal curing. Tests were conducted to evaluate compressive strength, autogenous shrinkage, length change, and freezing and thawing related to mass change, length change, and relative dynamic modulus of elasticity (RDME). In contrast to ASTM C157, which only measures drying shrinkage after 14 days of curing, autogenous shrinkage of concrete was measured in this study. KTMR-22, developed by the Kansas Department of Transportation, was used to evaluate freeze-thaw durability of internally cured repair mixtures because this method subjects test specimens to a much harsher test regimen than ASTM C666. For example, KTMR-22 utilizes 660 cycles that simulate 20 years of exposure to 33 cycles of freezing and thawing compared to ASTM-666 exposure of only 300 cycles. Results showed that the mixture made with lightweight aggregate and low cement content met all requirements for expansion and RDME. This mixture also had minimum autogenous shrinkage among all the mixtures.
Keywords: High Early Strength Concrete; Patching; Freezing and Thawing; Autogenous Shrinkage; Relative Dynamic Modulus of Elasticity